LITERASI DIGITAL SEBAGAI WUJUD PEMBERDAYAAN MASYARAKAT DI ERA GLOBALISASI - Bahri, Ahmad Syaiful; Izzah, Devi Khafidhotul; Hasanah, Febriyatul (Cahaya Ilmu Bangsa, 2025)
This article aims to provide an understanding of Digital Literacy as a Form of Community Empowerment in the Era of Globalization. This article was written by reviewing scientific literature such as articles from reputable journals and other sources that have been validated by the author. The benefits of this article are as a contribution to knowledge about community empowerment in the era of globalization which is linked to digital literacy. This article uses the literature study method in compiling this article, namely